AN ANALYSIS OF ONOMATOPOEIA IN WEBTOON COMIC: “PYRAMID GAME” - Hirvan, Fatiya Fahirani; Yusmalinda, Yusmalinda (STBA Prayoga Padang, 2024)
This study focuses on analyzing the types of onomatopoeia found in the webtoon comicPyramid Game. Onomatopoeia plays a significant role in graphic storytelling, as it bridgesthe gap between visual elements and auditory experiences. Using a qualitative researchmethod, this study examines the different types of onomatopoeia employed in the webtoon,categorizing them based on their specific functions and characteristics. The researchidentifies various types of onomatopoeic expressions based on Elizabeth (2024). By focusingsolely on the types of onomatopoeia, the study provides an in-depth understanding of howthese sound-based words contribute to the comic’s structure and reader immersion. The studyfound that the webtoon Pyramid Game features five distinct types of onomatopoeia:mechanical, fast motion, musical, food preparation and eating, and fighting onomatopoeia.However, animal-related onomatopoeia is notably absent from the webtoon. This may bebecause such sounds are typically associated with environments like zoos, while PyramidGame is set in a classroom. The findings highlight the diverse applications of onomatopoeiain Pyramid Game and underscore their significance in enhancing the comic's overallstorytelling and reader experience.